Reliability of a novel dynamic test of postural stability in high-level soccer players - Beelen, P. E.; Okhuijsen, R.; Prins, M. R.; Huurnink, A.; Hordijk, T.; Kruiswijk, K.; Goedhart, E. A.; van der Wurff, P.; Nolte, P. A.; van Dieën, J. H.; Kingma, I. (Heliyon, 2021)
Postural stability of athletes is commonly tested with single-leg stance (SLS) tests. However, for this population, these tests are insufficiently challenging to achieve high sensitivity. Therefore, a new dynamic SLS test based on standardized translational surface perturbations was developed. This study aimed to assess reliability, sensitivity to learning effects, and internal and concurrent validity of this novel test. Healthy soccer players (21 females, 21 males) performed 2 test sessions. Each session consisted of 2 trials. For one trial, the participant performed a 30-seconds, unperturbed SLS on each leg, followed by 12 platform perturbations per leg. Intraclass Correlation Coefficients (ICC) and correlations between outcomes were calculated for the Center of Pressure speed (CoPs) and Time To Stabilization (TTS). ANOVA was used to assess learning effects. CoPs and TTS showed a fair reliability between sessions (ICC = 0.73-0.76). All variables showed improvement over time within and between sessions (all p < 0.01) and were moderately correlated with CoPs during unperturbed SLS (r = 0.39-0.56). Single-leg dynamic postural stability testing through standardized horizontal platform perturbations yielded sufficiently reliable CoPs and TTS outcome measures in soccer players. The moderate correlations with unperturbed SLS support concurrent validity, but also indicates that the new test captures aspects of postural stability that differ from the conventional, unperturbed SLS test.